The Study of all the Optical, Electrical and the Performance Coefficients for the (Rhodamine B - Acriflavine) Laser Dyes Solar Cells Doped with Nanoparticles - Mithaq M. Mehdy Al- Sultani (Journal of Global Pharma Technology, 2016)
In this study of the effect of nanomaterials on the performance of Solar cells with laser dyes. The study included visual measurements of the dye solutions with different concentrations on the optical properties such as absorption and transmittance (A, T), the absorption coefficient, refractive index, reflectivity and optical conductivity at the wavelengths (400-800) nm. Using the UV-visible spectrum device, the value of the energy gap was calculated. The changing in the values of the previous variables the focus. The electrical properties as ( dielectric constant 14Îµ